# Calculator search results

Formula
Solve the equation
Graph
$y = - \left ( 7 - 2 x \right ) - 3 \left ( 9 - 5 x \right )$
$y = 0$
$x$Intercept
$\left ( 2 , 0 \right )$
$y$Intercept
$\left ( 0 , - 34 \right )$
$- \left( 7-2x \right) -3 \left( 9-5x \right) = 0$
$x = 2$
 Solve a solution to $x$
$- \left ( 7 - 2 x \right ) \color{#FF6800}{ - } \color{#FF6800}{ 3 } \left ( \color{#FF6800}{ 9 } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ x } \right ) = 0$
 Multiply each term in parentheses by $- 3$
$- \left ( 7 - 2 x \right ) \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 9 } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 5 } \right ) \color{#FF6800}{ x } = 0$
$\color{#FF6800}{ - } \left ( \color{#FF6800}{ 7 } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \right ) - 3 \times 9 - 3 \times \left ( - 5 \right ) x = 0$
 Change the symbol of each term in parentheses when there is a (-) symbol in front of parentheses 
$\color{#FF6800}{ - } \color{#FF6800}{ 7 } + \color{#FF6800}{ 2 } \color{#FF6800}{ x } - 3 \times 9 - 3 \times \left ( - 5 \right ) x = 0$
$- 7 + 2 x \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 9 } - 3 \times \left ( - 5 \right ) x = 0$
 Multiply $- 3$ and $9$
$- 7 + 2 x \color{#FF6800}{ - } \color{#FF6800}{ 27 } - 3 \times \left ( - 5 \right ) x = 0$
$- 7 + 2 x - 27 \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 5 } \right ) \color{#FF6800}{ x } = 0$
 Simplify the expression 
$- 7 + 2 x - 27 + \color{#FF6800}{ 15 } \color{#FF6800}{ x } = 0$
$\color{#FF6800}{ - } \color{#FF6800}{ 7 } + 2 x \color{#FF6800}{ - } \color{#FF6800}{ 27 } + 15 x = 0$
 Find the sum of the negative numbers 
$\color{#FF6800}{ - } \color{#FF6800}{ 34 } + 2 x + 15 x = 0$
$- 34 + \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 15 } \color{#FF6800}{ x } = 0$
 Calculate between similar terms 
$- 34 + \color{#FF6800}{ 17 } \color{#FF6800}{ x } = 0$
$\color{#FF6800}{ - } \color{#FF6800}{ 34 } \color{#FF6800}{ + } \color{#FF6800}{ 17 } \color{#FF6800}{ x } = 0$
 Organize the expression 
$\color{#FF6800}{ 17 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 34 } = 0$
$17 x \color{#FF6800}{ - } \color{#FF6800}{ 34 } = 0$
 Move the constant to the right side and change the sign 
$17 x = \color{#FF6800}{ 34 }$
$\color{#FF6800}{ 17 } \color{#FF6800}{ x } = \color{#FF6800}{ 34 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \color{#FF6800}{ 2 }$
 그래프 보기 
Graph
Solution search results